VO2 responses to intermittent swimming sets at velocity associated with VO2max - Libicz, S.; Roels, B.; Millet, G. P. (Canadian Journal of Applied Physiology, 2005)
While the physiological adaptations following endurance training are relatively well understood, in swimming there is a dearth of knowledge regarding the metabolic responses to interval training (IT). The hypothesis tested predicted that two different endurance swimming IT sets would induce differences in the total time the subjects swam at a high percentage of maximal oxygen consumption (VO2max). Ten trained triathletes underwent an incremental test to exhaustion in swimming so that the swimming velocity associated with VO2max (vVO2max) could be determined. This was followed by a maximal 400-m test and two intermittent sets at vVO2max: (a) 16 x 50 m with 15-s rest (IT50); (b) 8 x 100 m with 30-s rest (IT100). The times sustained above 95% VO2max (68.50 ± 62.69 vs. 145.01 ± 165.91 sec) and 95% HRmax (146.67 ± 131.99 vs. 169.78 ± 203.45 sec, p = 0.54) did not differ between IT50 and IT100 (values are mean ± SD). In conclusion, swimming IT sets of equal time duration at vVO2max but of differing work-interval durations led to slightly different VO2 and HR responses. The time spent above 95% of VO2max was twice as long in IT100 as in IT 50, and a large variability between mean VO2 and HR values was also observed.